Sistem Monitoring Tekanan Pada Pipa Air Menggunakan Arduino Uno Pada Jaringan Lora 920-923 Mhz - Sigit Pramono; Prasetyo Yuliantoro; Savena Rinda Pamungkas (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
In everyday life water is one of the components that is very important and becomes a basic need for human life and other living things. Of course, when flowing water to all corners there are obstacles such as leaks in water pipes that can be caused by air pressure. These leaks can cause the flowing water to get dirty or even not flow all the way to the destination. Therefore, this study will be created a pressure monitoring system on water pipes that will use pressure transmitter sensors that serve to read the pressure on water pipes using LoRaWAN data communication, this communication is used because the device can communicate up to a distance of 5 to 15 kilometers. To connect or send data from the sensor to LoRa requires an Arduino uno that will process the data from the sensor to be used. To store data using the Antares platform. This research is useful for monitoring pressure on water pipes and minimizing leaks in pipes. By using the method of calculating linear regression equations obtained a very accurate value for water pressure readings on pressure sensors that are 98.9%, while the results of testing the values received signal strength indicator (RSSI), signal noise radio (SNR) and packet loss are interconnected, in the value of RSSI and SNR the smaller the packet loss the more data is lost. The use of Spreading Factor values can also be taken into account if you want a longer range with a small packet loss result.